2009
DOI: 10.1007/s12665-009-0299-7
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia adsorption and nitritation in sediments derived from the Three Gorges Reservoir, China

Abstract: The influences of suspended particles (SPs) on NH 4? adsorption and nitritation occurring in the water system of the Three Gorges Reservoir (TGR) were evaluated in this study. The results indicated that the adsorption of NH 4 ? was significantly affected by the SPs concentration under the conditions typically present in the TGR. The amount of ammonia adsorbed per unit weight of suspended particles was inverse proportional to the concentration of suspended particles. However, the influences of the particle size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Studies suggest that particle association can provide microorganisms with benefits such as protection against predators, enhanced environmental resistance, and increased nutrient availability . Previous research posited that nitrifying microorganisms were attached to particles based on indirect evidence . As expected, the particle concentration experiment showed that ammonia removal rate, NO 2 − + NO 3 − accumulation rate, and abundance of AOA and AOB amoA genes were significantly affected by increasing particle concentration (Table ; Figures a and a).…”
Section: Discussionsupporting
confidence: 53%
“…Studies suggest that particle association can provide microorganisms with benefits such as protection against predators, enhanced environmental resistance, and increased nutrient availability . Previous research posited that nitrifying microorganisms were attached to particles based on indirect evidence . As expected, the particle concentration experiment showed that ammonia removal rate, NO 2 − + NO 3 − accumulation rate, and abundance of AOA and AOB amoA genes were significantly affected by increasing particle concentration (Table ; Figures a and a).…”
Section: Discussionsupporting
confidence: 53%
“…The positive correlation between TSM and nitrification has been addressed in freshwater systems (Xia et al, 2009;Wang et al, 2010) and in the relatively turbid region of estuaries, where nitrification activities were found to be higher (Berounsky et al, 1993, Helder andDevries, 1983), especially in the zone of estuarine turbidity maxima (Owens, 1986). Moreover, a similar correlation was found in the oxygen minimum zone (Woebken et al, 2007;Galand et al, 2008) though the particulate organic matter (POM) concentration was much lower.…”
Section: Suspended Particlesmentioning
confidence: 89%
“…Recent culture-based and field experiments in freshwater and marine upwelling systems revealed that both ammonia and nitrite oxidizers tend to attach to particles where ammonium adsorption may occur to stimulate nitrification (Xia et al, 2009;Wang et al, 2010;Fussel et al, 2012). One distinctive feature of Asian rivers is that enhanced nutrient fluxes are often accompanied by huge amounts of suspended sediments sourced from soil erosion (Syvitski et al, 2005;Milliman and Syvitski, 1992), resulting in highly turbid coastal and shelf water (e.g., the East China Sea shelf satellite images in Fig.…”
Section: S S-y Hsiao Et Al: Nitrification and Its Oxygen Consumptionmentioning
confidence: 99%
“…7.6 (Wang et al, 2010) indicated that the seven locations were divided into 2 sets, which was similar to the grouping based on the microbial community construction. The data of these ratios were used to group the aquatic environment using cluster analysis.…”
Section: Fig 75 Distribution Ratios Of Functional Bacteria In Diffementioning
confidence: 78%
“…Table 7.5 shows the average, maximum, minimum number of cells and coefficient of variation (CV) in surface water, bottom water and sediments from the seven locations (Wang et al, 2010). Table 7.5 shows the average, maximum, minimum number of cells and coefficient of variation (CV) in surface water, bottom water and sediments from the seven locations (Wang et al, 2010).…”
Section: Abundance Of Functional Bacteria In Aquatic Environmentsmentioning
confidence: 99%